A Generalized Differential Colorimetric Interferometry Method: Extension to the Film Thickness Measurement of Any Point Contact Geometry. Issue 4 (4th July 2018) - Wheeler, Jean-David; Molimard, Jérôme; Devaux, Nicolas; Philippon, David; Fillot, Nicolas; Vergne, Philippe; Morales-Espejel, Guillermo E.
ABSTRACT: Whereas industrial elastohydrodynamic (EHD) contacts are generally noncircular, most experimental observations are made on sphere-on-plane conjunctions. The circular case is indeed a specific elliptical case, and it was widely investigated. The differential colorimetric interferometry (DCI) technique was often used to perform precise film thickness measurements in circular EHD contacts. From a single picture of the dynamic contact, it enables mapping the film thickness of the full conjunction, and postprocessing can be applied afterwards. Moreover, it is possible to record sequences at relatively high-frequency sampling. However, until now, the method could not be directly applied to noncircular conjunctions. In the present article, a generalized DCI method is proposed and assessed by several static and EHD validation cases for elliptical and torus-on-plane contact geometries. This new method no longer necessitates particular requirements on the contact shape while retaining the advantages of the original DCI method. It allows precise film thickness measurements in realistic industrial EHD contacts and opens the way for new experimental observations.